Crowdsourcing to manage service gaps in service networks. Issue 7 (22nd July 2019) - Blair, Amanda; Key, Thomas Martin; Wilson, Matthew
Abstract : Purpose: The purpose of this paper is to illustrate and conceptualize how crowdsourcing can be implemented as a potential means to address gaps in service quality within service networks and to provide guidance to marketing practitioners on the use of crowdsourcing within service networks. Design/methodology/approach: This paper conceptualizes how crowdsourcing can be used to address service quality gaps in service networks and provides propositions regarding the effects of crowdsourcing on service quality gaps. Findings: Conceptual paper with a literature review, suggested a model for service quality gaps in service networks and propositions regarding the effects of crowdsourcing to manage service quality gaps. Research limitations/implications: This research contributes to the literature on crowdsourcing by theorizing how crowdsourcing impacts service quality in service networks. Practical implications: Considerations for managers implementing crowdsourcing strategies and activities within service networks are provided. In particular, implications with regard to forming the crowd, developing the most appropriate approach and integrating value into the firm are discussed. Originality/value: This paper offers an original contribution linking crowdsourcing to service quality.